Selective Cleavage at CCA Ends and Anticodon Loops of tRNAs by Stress-Induced RNases - Akiyama, Yasutoshi; Lyons, Shawn M.; Fay, Marta M.; Tomioka, Yoshihisa; Abe, Takaaki; Anderson, Paul J.; Ivanov, Pavel (Frontiers in Molecular Biosciences, 2022)
Stress-induced tRNA cleavage has been implicated in various cellular processes, where tRNA fragments play diverse regulatory roles. Angiogenin (ANG), a member of the RNase A superfamily, induces cleavage of tRNAs resulting in the formation of tRNA-derived stress-induced RNAs (tiRNAs) that contribute to translational reprogramming aiming at cell survival. In addition to cleaving tRNA anticodon loops, ANG hass been shown to cleave 3'-CCA termini of tRNAs in vitro, although it is not known whether this process occurs in cells. It has also been suggested that tiRNAs can be generated independently of ANG, although the role of other stress-induced RNases in tRNA cleavage is poorly understood. Using gene editing and biochemical approaches, we examined the involvement of ANG in stress-induced tRNA cleavage by focusing on its cleavage of CCA-termini as well as anticodon loops. We show that ANG is not responsible for CCA-deactivation under sodium arsenite (SA) treatment in cellulo, and although ANG treatment significantly increases 3'-tiRNA levels in cells, the majority of 3'-tiRNAs retain their 3'-CCA termini. Instead, other RNases, can cleave CCA-termini in cells, although with low efficiency. Moreover, in the absence of ANG, other RNases are able to promote the production of tiRNAs in cells. Depletion of RNH1 (an endogenous inhibitor of RNase A superfamily) promotes constitutively-produced tiRNAs and CCA-deactivated tRNAs in cells. Interestingly, SA treatment in RNH1-depleted cells did not increase the amount of tiRNAs or CCA-deactivated tRNAs, suggesting that RNase A superfamily enzymes are largely responsible for SA-induced tRNA cleavage. We show that interplay between stress-induced RNases cause targeting tRNAs in a stress-specific manner in cellulo.